2009
DOI: 10.1523/jneurosci.4772-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

The GABRG2 Mutation, Q351X, Associated with Generalized Epilepsy with Febrile Seizures Plus, Has Both Loss of Function and Dominant-Negative Suppression

Abstract: The GABA A receptor ␥2 subunit mutation, Q351X, associated with generalized epilepsy with febrile seizures plus (GEFSϩ), created a loss of function with homozygous expression. However, heterozygous ␥2(ϩ/Ϫ) gene deletion mice are seizure free, suggesting that the loss of one GABRG2 allele alone in heterozygous patients may not be sufficient to produce epilepsy. Here we show that the mutant ␥2 subunit was immature and retained in the endoplasmic reticulum (ER). With heterozygous coexpression of ␥2S/␥2S(Q351X) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(135 citation statements)
references
References 38 publications
7
128
0
Order By: Relevance
“…A similar hyperekplexia-like phenotype was observed in the GlyR mouse mutant oscillator, resulting from lack of GlyR expression due to introduction of a premature stop codon at amino acid position 355 (21). Loss of receptor proteins has also been found in other channelopathies, such as GEFSϩ (generalized epilepsy with febrile seizures plus) associated with truncated GABA A receptor variants (27).…”
Section: Discussionmentioning
confidence: 67%
“…A similar hyperekplexia-like phenotype was observed in the GlyR mouse mutant oscillator, resulting from lack of GlyR expression due to introduction of a premature stop codon at amino acid position 355 (21). Loss of receptor proteins has also been found in other channelopathies, such as GEFSϩ (generalized epilepsy with febrile seizures plus) associated with truncated GABA A receptor variants (27).…”
Section: Discussionmentioning
confidence: 67%
“…For instance, injection of LPS into cortex produces focal epileptiform discharges within 5 min after stimulation (79). Fever, a symptom of inflammation, is known to promote febrile seizures in infants or mice with appropriate genetic backgrounds (80). Our work now provides the basis to understand the molecular and cellular cascades by which inflammation triggers seizures.…”
Section: Discussionmentioning
confidence: 89%
“…The GABRG2 gene, covering 87 897 bp, is at 5q31.1-q33.1 and two SNPs that we will consider, rs211014 and rs211013, map to intron 8. This gene has also been associated with epilepsy and febrile seizures (Kang et al, 2009). Linkage and association studies have reported, for example, that the 5q34 GABA A receptor genes were involved in AD risk in Finns (Radel et al, 2005), and the 5q33 GABA A receptor genes were associated with HD in Chinese subjects (Loh et al, 2007).…”
Section: Chromosome 5 Gaba a Receptor Gene Clustermentioning
confidence: 99%